Minimum Age Requirements and the Impact of School Choice - Julio Cáceres-Delpiano; Eugenio P. Giolito (Institute of Labor Economics (IZA), 2018)
Using several data sources from Chile, we study the impact of school choice at the time of starting primary school. To study the contribution of school choice, we exploit the combination of multiple cutoffs defining the minimum age at entry, and the difference across municipalities in the composition of the schools according to these cutoffs. Children living in the same municipality, and whose birthday differs by a few days not only have their incentives to delay school entry affected, but also face, in case of not delaying, a different set of schools. We show that a larger set of schools increases the probability of starting in a better school, measured by non high-stakes examination. Moreover, this quasi-experimental variation reveals an important reduction in the likelihood of dropping out, and a reduction in the probability that a child would switch schools during her/his school life. Secondly, for a subsample of students who have completed high school, we observe that a larger school choice at the start of primary school increases students' chance of taking the national examination required for higher education and the likelihood of being enrolled in a selective college.
Keywords: A21; I24; I25; I28; 330; age requirements; school choice